Mitigasi Bencana Gunung Merapi Berbasis Sistem Informasi Spasial Di Nagari Canduang Koto Laweh Kabupaten Agam - Alexander Syam; Tiara Suci Ramadani (Kilau Publishing, 2026)
Mount Marapi in West Sumatra is one of the most active volcanoes on the island of Sumatra. Since 1979, it has erupted several times, often causing material losses and even fatalities. The most recent eruption occurred from 2023 to early 2024 and resulted in 24 deaths. Therefore, its status remains at Level II, or Alert Level, because it may erupt at any time, as occurred in the latest eruption. Referring to the identification results regarding the eruption hazards of Mount Marapi, appropriate disaster mitigation measures need to be formulated. Mitigation is carried out to minimize the damage caused by disasters and to reduce the number of casualties. Nagari Canduang Koto Laweh does not yet have data on the vulnerability to Mount Marapi hazards or an appropriate mitigation direction map. Therefore, this research is necessary and important. This study aims to identify the spatial distribution of potential volcanic eruption hazards using spatial analysis, analyze the level of vulnerability based on physical, social, economic, and environmental aspects, and formulate mitigation directions in the form of a Mount Marapi volcanic disaster mitigation map. The method used combines quantitative methods, including Geographic Information Systems (GIS), and qualitative methods. Based on the results of the vulnerability analysis, the area of Nagari Canduang Koto Laweh affected within the Mount Marapi Volcanic Disaster-Prone Area Map is 188.95 hectares and is classified as Zone I. This zone has the potential to be affected by cold lava flows, ashfall, and possible incandescent rock ejection within a 7 km radius. The level of vulnerability, viewed from physical, social, economic, and environmental aspects, particularly in Nagari Canduang Koto Laweh, is categorized as low. The recommended disaster mitigation directions for Mount Marapi, based on the level of vulnerability, are directed toward SD Negeri 15 Anak Kampung, SD Negeri 05 Limo Suku Bawah, and SMP Negeri 2 Canduang.